Imaging and biodistribution of radiolabeled SP90 peptide in BT-483 tumor bearing mice. (July 2020) - Lo, Wei-Lin; Liang, Chen-Hsien; Chen, Liang-Cheng; Lee, Shih-Ying; Lo, Sheng-Nan; Chen, Ming-Wei; Lu, Ruei-Min; Liu, I-Ju; Wu, Han-Chung; Chang, Chih-Hsien
Abstract: The objective of this study was to evaluate radiolabeled DOTA-SP90 as a radiotracer for breast cancer. The in vitro competition assay showed that radiolabeled DOTA-SP90 had significant binding affinity to BT-483 cancer cells. Biodistribution, nanoSPECT/CT and nanoPET/CT imaging results indicated that radiolabeled DOTA-SP90 can accumulate in tumors. In addition, radiolabeled DOTA-SP90 peptides can also detect metastatic tumors. Therefore, radiolabeled SP90 peptide may provide the potential capability as diagnostic agent for breast cancer patients. Highlights: Radiolabeled DOTA-SP90 peptide was developed as a radiotracer for breast cancer. The biodistribution results indicated that the accumulation of radiolabeled DOTA-SP90 in tumors. NanoSPECT/CT and nanoPET/CT showed that radiolabeled DOTA-SP90 accumulated in subcutaneous and metastatic tumors.